Enhanced inhibition of Pseudomonas aeruginosa virulence factor production and biofilm development by sublethal concentrations of eugenol and phenyllactic acid. (23rd August 2022) - Shariff, M.; Chatterjee, M.; Morris, S.D.; Paul, V.; Vasudevan, A.K.; Mohan, C.G.; Paul‐Prasanth, B.; Biswas, R.
Abstract: Biofilm development in Pseudomonas aeruginosa is regulated by its quorum sensing (QS) systems. It has three major QS systems: LasI/R, RhlI/R and PQS/MvfR. Previous studies showed that phenyllactic acid (PLA) binds to RhlR and PqsR and inhibits the Rhl and PQS QS; and eugenol at sublethal concentration inhibits Las and PQS QS systems. Here, we have demonstrated that a combination of sublethal doses of eugenol and PLA enhanced the inhibition of the QS mediated production of the virulence factors and biofilm development of this pathogen. A combination of 50 μmol l −1 eugenol and 0·3 mmol l −1 PLA significantly inhibited the pyocyanin production, protease activity, swarming motility and cytotoxic activities of P. aeruginosa strain PAO1, whereas eugenol and PLA when added individually to PAO1 cultures were less effective in inhibiting its virulence factor expression. Biofilm formation of PAO1 was reduced by 32, 19 and 87% on glass surfaces; and 54, 49 and 93% on catheter surfaces when treated using 50 μmol l −1 eugenol or 0·3 mmol l −1 PLA and their combinations, respectively. The in vitro finding in the reduction of biofilm development was further validated in vivo using a catheter associated medaka fish biofilm model. Our results indicate that a combination of QS inhibitors targeting different QS pathways should be selected while designing therapeutic molecules to achieve maximum QS mediated biofilm inhibition and clinical outcome against P. aeruginosa . Abstract : Significance and Impact of the Study: Pseudomonas aeruginosa is a Gram negative opportunistic pathogen. Its biofilm infections are difficult to treat with antibiotics. It is therefore important to identify effective and new drug molecules or repurpose existing drug molecules for effective treatment of biofilm infections of this pathogen. Biofilm formation of P. aeruginosa is regulated by its three major quorum sensing (QS) systems. Here, we demonstrated that a combination of sublethal doses of eugenol and PLA synergistically inhibits all three QS systems and biofilm development of P. aeruginosa . Our results highlight the importance of targeting different QS pathways for achieving maximum biofilm inhibition of P. aeruginosa .